2008
DOI: 10.1177/0731684407085644
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Prediction of Erosion Response of Glass Reinforced Polyester-Flyash Composites

Abstract: Solid particle erosion of polymer composites is a complex surface damage process, strongly affected by material properties and operational conditions. To avoid repeated experimentation, it is important to develop predictive equations to assess material loss due to erosion wear under any impact conditions. This paper presents the development of a mathematical model for estimating erosion damage caused by solid particle impact on flyash filled glass fiber reinforced polyester composites. The model is based upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Various reports are also available on the solid particle erosion wear response of polymer composites filled with ceramic powder such as Al 2 O 3 , SiC, etc. . Taguchi's experimental design has been used to study the wear response of polymer matrix composites by many authors .…”
Section: Introductionmentioning
confidence: 99%
“…Various reports are also available on the solid particle erosion wear response of polymer composites filled with ceramic powder such as Al 2 O 3 , SiC, etc. . Taguchi's experimental design has been used to study the wear response of polymer matrix composites by many authors .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the void fractions in the composites also increased with the integration of iron‐mud content. Irrespective of the filler type, glass‐epoxy composites also showed similar trends . Difference in measured and theoretical density values of composite is termed as void content, which has significant effects on its certain mechanical properties.…”
Section: Resultsmentioning
confidence: 82%
“…Such multi-component composites consisting of a matrix phase reinforced with a fiber and filled with particulate matters are termed as hybrid composites. Some recent publications by Patnaik et al [114][115][116][117][118][119][120][121][122] have reported extensively on erosion wear characteristics of glass-polyester hybrid composites filled with different particulate fillers such as fly ash, aluminium oxide (Al 2 O 3 ), and silicon carbide (SiC). These reports suggested that in fiber reinforced particulate filled hybrid composites, the rate of material loss due to solid particle erosion reduced significantly with the addition of hard particulate fillers into the matrix.…”
Section: Erosion Of Hybrid Compositesmentioning
confidence: 99%